Team Assisted Individualization TAI (Team Assisted Individualization) Learning Model on Learning Skills of Private Elementary School Students PAB 29 Manunggal - Nabila, Puput (Journal of Elementary School Education, 2023)
This study aims to: (1) Know the listening skills of fourth grade students at Sekolah Dasar PAB 29 Manunggal before using the TAI (Team Assisted Individualization) learning model, (2) Know the listening skills of fourth grade students at SD PAB 29 Manunggal Private Elementary School after using the TAI learning model ( Team Assisted Individualization), (3) Knowing the effect of the TAI (Team Assisted Individualization) learning model on the listening skills of grade IV Sekolah Dasar Private PAB 29 Manunggal. This type of research is a quantitative study with a one-group pretest-posttest design. The population of this study was class IV-B of PAB 29 Manunggal Private Elementary School, which consisted of28 people. The sampling technique used is saturated sampling in which all members of the population are used as samples.Data collection techniques using observation sheets. Based on the results of the study: (1) Before using the TAI (Team Assisted Individualization) learning model, the average student score was still low, namely 51.79 and the highest scoreobtained by students before using the TAI (Team Assisted Individualization) learning model was 65, (2 ) After using the TAI (Team Assisted Individualization) learning model the average value of students increased to 79.57, and the highest score obtained by students after using the TAI (Team Assisted Individualization) learning model was 94, (3) Based on this research, the results obtained Hypothesis calculations using the t test (Paired Sample T Test) at a significant level of 0.05 obtained sig. (2-tailed) is 0.000 ≤ 0.05, it can be said that Ha is accepted and H0 is rejected.